Investigation of the anti-salmonellal and antiplasmodial properties of leaf extracts of Rourea coccinea Beninese medicinal plant - KPADONOU-KPOVIESSI, Bénédicta; KPOVIESSI, D. S. Salomé; AGNIMONHAN, Finagnon H.; GOUETI, Basile (My University, 2023)
Rourea coccinea, also called Byrsocarpus coccineus is a medicinal plant widely used in primary health care in West Africa and in this case in Benin. In the present study, the hydroethanolic extract of these leaves was investigated for its anti-salmonella and antiplasmodial properties. The evaluation of anti-salmonella activity was carried out by the micro dilution method associated with resazurine while that of antiplasmodial activity by method described by Syber Green. Minimum inhibitory concentrations (MICs) of the hydroethanolic extract against Salmonella strains were higher than 2000 μg/mL. This extract was active against multidrug-resistant Plasmodium falciparum strains (PfDd2) with an inhibitory concentration (IC50) of 32.26 μg/mL. These works on Rourea coccinea justify that the plant has a clearly remarkable antiplasmodial activity rather than anti-salmonella one and its use in traditional medicine to treat malaria in Benin
Keywords: Rourea coccinea; leaves; hydroethanolic extract; Salmonella strains; Plasmodium falciparum; malaria.